The emerging nanomedicine-based technology for non-small cell lung cancer immunotherapy: how far are we from an effective treatment - Peng, Lei; Xu, Quan; Yin, Sui; Zhang, Ye; Wu, Hao; Liu, Yangchun; Chen, Liru; Hu, Yeji; Yuan, Jun; Peng, Kai; Lin, Qin (Frontiers in Oncology, 2023)
Non-small cell lung cancer (NSCLC) is a prominent etiology of cancer-related mortality. The heterogeneous nature of this disease impedes its accurate diagnosis and efficacious treatment. Consequently, constant advancements in research are imperative in order to comprehend its intricate nature. In addition to currently available therapies, the utilization of nanotechnology presents an opportunity to enhance the clinical outcomes of NSCLC patients. Notably, the burgeoning knowledge of the interaction between the immune system and cancer itself paves the way for developing novel, emerging immunotherapies for treating NSCLC in the early stages of the disease. It is believed that with the novel engineering avenues of nanomedicine, there is a possibility to overcome the inherent limitations derived from conventional and emerging treatments, such as off-site drug cytotoxicity, drug resistance, and administration methods. Combining nanotechnology with the convergence points of current therapies could open up new avenues for meeting the unmet needs of NSCLC treatment.